2013
DOI: 10.3109/13880209.2013.767362
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of saffron (Crocus sativus) against lethal ventricular arrhythmias induced by heart reperfusion in rat: A potential anti-arrhythmic agent

Abstract: Context: Saffron (Crocus sativus L.) has been used as a cuisine spice in eastern and western societies for thousands of years. In traditional medicine, saffron is recommended for the treatment of various kinds of disorders including heart palpitations. Objective: We investigated the hypothesis of the protective effect of saffron on lethal cardiac arrhythmias induced by heart ischemia-reperfusion in rat. Materials and methods: Animals were divided into a control (CTL) group that received tap water, Saf50, Saf10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…The cardioprotective effects of saffron and its constituents were evaluated previously in various aspects (Joukar et al, ; Joukar, Ghasemipour‐Afshar, Sheibani, Naghsh, & Bashiri, ; Khori et al, ; Razavi, Hosseinzadeh, Movassaghi, Imenshahidi, & Abnous, ). However, based on our literature review, there is no human study carried out yet to evaluate the saffron impacts on the atherogenesis‐related genes.…”
Section: Discussionmentioning
confidence: 99%
“…The cardioprotective effects of saffron and its constituents were evaluated previously in various aspects (Joukar et al, ; Joukar, Ghasemipour‐Afshar, Sheibani, Naghsh, & Bashiri, ; Khori et al, ; Razavi, Hosseinzadeh, Movassaghi, Imenshahidi, & Abnous, ). However, based on our literature review, there is no human study carried out yet to evaluate the saffron impacts on the atherogenesis‐related genes.…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian's traditional medicine, ointments containing saffron are used to treat hot palpitation of heart [4]. Scientific studies have confirmed the validity of saffron extracts in the treatment of mild to moderate depression [5,6], and agent against erectile dysfunction [7], and as anti-arrhythmic agent and restorer of cardicac functions [8,9]. Other studies showed a role of saffron as a protector against age related macular degeneration [10,11], in reducing cognitive decline in patients with Alzheimer Disease [12,13], and as a source for potential anti-cancer agents [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, it is recommended to treat arteriosclerosis, hypertension, acute coronary syndrome and also heart palpitations . In addition, experimental studies revealed its protective effect against chemical and ischaemia–reperfusion myocardial injuries and its antiarrhythmic properties. Pretreatment with aqueous extract of saffron reduced the episodes and duration of life‐threatening ventricular arrhythmia such as ventricular tachycardia and fibrillation and the score of cardiac arrhythmia in rat .…”
Section: Introductionmentioning
confidence: 99%